High-entropy lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
By introducing transition metal elements into the lithium manganese iron phosphate positive electrode material, and using the high-entropy lithium manganese iron phosphate preparation method, the problems of insufficient ginger Taylor effect and conductivity of manganese elements are solved, the excellent cycle stability and electrochemical performance of the material are achieved, and the production process is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202411876202.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium manganese iron phosphate (LMFP) cathode materials are prone to the ginger Taylor effect of manganese elements during charging and discharging, resulting in a reduced cycle life and insufficient conductivity, which affects the rate performance and power density.
By introducing one to three other transition metal elements besides manganese, the preparation method of high-entropy lithium manganese phosphate is adopted, and the precise solid phase sintering method of three grinding and one stirring is used to form a stable single-phase solid solution structure, inhibiting the ginger Taylor effect of manganese elements and improving the conductivity of the material.
The excellent cycle stability and electrochemical performance of high-entropy lithium manganese iron phosphate cathode material is achieved, the 150 cycle capacity retention rate is as high as 98%, and the production process is simplified, the cost is reduced, and it has good industrial production and economic benefits.
Smart Images

Figure CN119674015A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion battery energy storage, and in particular to a high-entropy lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] With the popularity of electric vehicles and renewable energy, the demand for efficient and environmentally friendly batteries is growing. In order to better meet market needs and promote the replacement of new energy storage devices, energy density must be further improved. Lithium manganese iron phosphate (LMFP) is considered to be a strong competitor for the next generation of lithium-ion battery cathode materials due to its high theoretical capacity, good cycle stability and safety. Compared with lithium iron phosphate (LFP), due to the Mn 2+ / Mn 3+ The corresponding 4.1V redox potential is higher than the 3.4V of LFP, so manganese doping effectively improves the energy density of LFP, and the higher the manganese content, the higher the energy density. The actual energy density can be increased by 15%-20%, which gives LMFP a clear advantage in terms of power battery life. In addition, LMFP and LFP both belong to the olivine structure and have stable PO4 tetrahedrons, which can provide reliable structural support during long-term charge and discharge cycles, giving LMFP excellent thermodynamic and kinetic stability. Therefore, as an upgraded alternative material to LFP, LMFP is an energy storage material with high energy density and high safety.
[0003] However, the Jan-Taylor effect and poor conductivity are huge obstacles in the application of LMFP. The inevitable Jan-Taylor effect of manganese will lead to the dissolution of manganese atoms during the charge and discharge process, seriously reducing the cycle life of the battery and possibly causing environmental pollution; the introduction of manganese further reduces the electronic conductivity and ion diffusion of LFP, resulting in obvious polarization under high current conditions, affecting its rate performance and power density, and the ion migration impedance of LMFP under low temperature conditions is significantly increased, which restricts its further widespread application. Particle nano-sizing can shorten the lithium ion migration path, and morphology design and structural regulation can improve the reaction activity of the positive electrode material, thereby improving the excellent electrochemical performance; ion doping causes vacancies in the LMFP lattice, changes the interatomic bond length, and thus improves the conductivity of the material itself; surface coating can inhibit the dissolution of manganese while optimizing the conductivity. In contrast, optimizing the intrinsic structure of LMFP is the most reliable improvement strategy. Although significant progress has been made in research, the production process is generally a combination of solution method and solid phase method, resulting in complex process, low efficiency and high cost.
[0004] Therefore, there is an urgent need for a simple preparation method to achieve the production and application of high-capacity and long-cycle lithium manganese iron phosphate positive electrode materials. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a high-entropy lithium manganese iron phosphate positive electrode material and a preparation method thereof. The method is simple and efficient, and the prepared material has excellent structural stability, significantly inhibits the Jan-Taylor effect, and improves the electrochemical performance.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] In the first aspect, the present invention provides a method for preparing high-entropy lithium manganese iron phosphate, comprising adding a lithium source, a manganese source, an iron source, and a phosphorus source into a mixing tank according to an atomic molar ratio, and adding a certain amount of a carbon source and an appropriate amount of a solution at the same time, and grinding at high speed until fully mixed; then adding the required transition metal atoms according to atomic percentage, and repeatedly grinding and mixing; after completion, drying the solid-liquid mixture at a high temperature to completely remove the liquid component to obtain a solid mixture; grinding the solid mixture for a third time to obtain a powdered sample, and then performing a low-temperature calcination and carbonization treatment to obtain a precursor; stirring the precursor and calcining it at a high temperature for a long time to finally obtain a high-entropy lithium manganese iron phosphate positive electrode material.
[0008] Furthermore, the atomic molar ratio of the lithium source, manganese source, iron source and phosphorus source is in the range of 1.05:0.2:0.8:1 to 1.05:0.8:0.2:1; and the added amount of the carbon source is 5%-20% of the total mass of the above raw materials.
[0009] Furthermore, during the first high-speed grinding process, the rotation speed of the high-speed grinding is between 350 rpm and 500 rpm, and the time is within the range of 5 hours to 10 hours.
[0010] Among them, the initial grinding needs to mix the raw materials evenly and avoid oxidation.
[0011] Furthermore, the types of transition metal atoms required include Ti, Mg, Mo, Nb, Al, Cu, Ni, etc.; the total atomic percentage of transition metals is 1% to 10%.
[0012] Further, the rotation speed of the repeated grinding is between 350 rpm and 500 rpm, and the time is in the range of 5 hours to 10 hours.
[0013] Among them, the purpose of grinding again is to integrate the transition metal atoms into the iron atoms and manganese atoms and mix them evenly.
[0014] Furthermore, in the method for preparing high entropy lithium manganese iron phosphate, the drying temperature is between 80° C. and 160° C., and the drying time is between 12 hours and 48 hours.
[0015] Furthermore, the rotation speed of the third grinding is between 100 rpm and 200 rpm, and the time is in the range of 10 minutes to 30 minutes; the temperature of the low-temperature calcination is between 300° C. and 400° C., and the time is between 3 hours and 6 hours.
[0016] Furthermore, during the sample treatment process after the pre-calcination, the stirring speed is between 50 rpm and 100 rpm, and the time is between 1 minute and 5 minutes.
[0017] Furthermore, the high temperature calcination temperature is 600° C. to 800° C., and the time is 5 hours to 12 hours.
[0018] Furthermore, the lithium source is one of lithium carbonate, lithium acetate, lithium oxalate, and lithium hydroxide, the manganese source is one of manganese acetate, manganese carbonate, and manganese oxide, the iron source is one of ferroferric oxide, ferrous oxalate, and ferrous oxide, the phosphorus source is one of diammonium hydrogen phosphate, lithium phosphate, and phosphorus pentoxide, the carbon source is one of glucose, sucrose, oxalic acid, polyvinyl pyrrolidone, polyethylene glycol, and salicylic acid, and the solution is one of ethanol, ethylene glycol, acetone, and deionized water.
[0019] Furthermore, the transition metal atom Ti source is one of titanium dioxide, tetrabutyl titanate, titanium carbide, and titanium fluoride; the transition metal atom Mg source is one of magnesium carbonate, magnesium oxalate, magnesium acetate, and magnesium metaborate; the transition metal atom Mo source is one of molybdenum acetylacetonate, molybdenum carbide, molybdenum fluoride, and ammonium molybdate; the transition metal atom Nb source is one of niobium oxide, niobium pentachloride, and niobium oxalate; the transition metal atom Al source is one of aluminum acetylacetonate, aluminum metaphosphate, aluminum nitrate, and aluminum dihydrogen phosphate; the transition metal atom Cu source is one of copper citrate, copper pyrophosphate, copper acetylacetonate, and copper oxide; and the transition metal atom Ni source is one of nickel hydroxide, nickel acetylacetonate, nickel oxide, and nickel acetate.
[0020] In a second aspect, the present invention provides a high entropy lithium manganese iron phosphate positive electrode material prepared by the above method.
[0021] In a third aspect, the present invention provides an application of the high entropy lithium manganese iron phosphate positive electrode material in the preparation of a positive electrode for a lithium battery.
[0022] The beneficial effects of the present invention are:
[0023] 1) Based on the traditional LFP preparation, the present invention prepares a unique high-entropy lithium manganese iron phosphate positive electrode material by introducing one to three transition metal elements other than manganese; the high-entropy material increases the mixing entropy of the system and forms a stable single-phase solid solution structure; the different atomic sizes and bond energies of different elements can be used to strengthen the interaction between transition metal-O and effectively inhibit the Jan-Taylor effect of manganese; the synergistic effect of different doping atoms further improves the ion / electron transport capacity and enhances the electrochemical reaction kinetics.
[0024] 2) The high-entropy lithium manganese iron phosphate prepared by the present invention has a capacity retention rate of up to 98% in 150 cycles, showing excellent cycle stability.
[0025] 3) The mechanical mixing solid phase sintering process adopted by the present invention has simple process conditions, is easy to control, and is easy to realize large-scale industrial production; under the reducing effect of the carbon source, a cheap trivalent iron source can be used to replace a divalent iron source, thereby reducing production costs; the solution can be recycled, is green and environmentally friendly, and has great economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 XRD pattern of the high entropy lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0028] Figure 2 This is a Raman graph of the high entropy lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0029] Figure 3 This is an XPS graph of the high entropy lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0030] Figure 4 This is a SEM image of the high entropy lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0031] Figure 5 This is the electrochemical long cycle diagram of the high entropy lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention at a current density of 0.2C. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with the accompanying drawings and specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] The Jan-Taylor effect and insufficient conductivity of LMFP are huge obstacles to its development, and the complex production process further restricts its wide application. The inventors used lithium salts, phosphorus sources, carbon sources and various transition metal elements as raw materials, and prepared high-entropy lithium manganese iron phosphate materials through a precise solid-phase sintering method with three grindings and one stirring. As the positive electrode material of lithium-ion batteries, it has stable electrochemical properties. The technical solution is as follows:
[0034] The invention provides a preparation method of high-entropy lithium manganese iron phosphate, comprising the following steps: adding a lithium source, a manganese source, an iron source and a phosphorus source into a mixing tank according to an atomic molar ratio, adding a certain amount of a carbon source and an appropriate amount of a solution at the same time, and grinding at high speed until fully mixed; then adding required transition metal atoms according to atomic percentage, and repeatedly grinding and mixing; after completion, drying the solid-liquid mixture at high temperature to completely remove the liquid component to obtain a solid mixture; grinding the solid mixture for a third time to obtain a powdered sample, and then performing a low-temperature calcination and carbonization treatment to obtain a precursor; stirring the precursor and then calcining it at high temperature for a long time to finally obtain a high-entropy lithium manganese iron phosphate positive electrode material.
[0035] Preferably, the atomic molar ratio of the lithium source, manganese source, iron source and phosphorus source is in the range of 1.05:0.2:0.8:1 to 1.05:0.8:0.2:1; and the added amount of the carbon source is 5%-20% of the total mass of the above raw materials.
[0036] Preferably, during the first high-speed grinding process, the rotation speed of the high-speed grinding is between 350 rpm and 500 rpm, and the time is within the range of 5 hours to 10 hours.
[0037] Preferably, the types of transition metal atoms required include Ti, Mg, Mo, Nb, Al, Cu, Ni, etc.; the total atomic percentage of transition metals is 1% to 10%.
[0038] Preferably, the repeated grinding is performed at a rotation speed of 350 rpm to 500 rpm and for a time of 5 to 10 hours.
[0039] Preferably, in the method for preparing high entropy lithium manganese iron phosphate, the drying temperature is between 80° C. and 160° C., and the drying time is between 12 hours and 48 hours.
[0040] Preferably, the third grinding speed is between 100 rpm and 200 rpm, and the time is in the range of 10 minutes to 30 minutes; the low-temperature calcination temperature is between 300° C. and 400° C., and the time is between 3 hours and 6 hours.
[0041] Preferably, during the sample processing after the pre-calcination, the stirring speed is between 50 rpm and 100 rpm, and the time is between 1 minute and 5 minutes.
[0042] Preferably, the high temperature calcination temperature is 600° C. to 800° C., and the time is 5 hours to 12 hours.
[0043] In some preferred embodiments, the lithium source is one of lithium carbonate, lithium acetate, lithium oxalate, and lithium hydroxide, the manganese source is one of manganese acetate, manganese carbonate, and manganese oxide, the iron source is one of ferroferric oxide, ferrous oxalate, and ferrous oxide, the phosphorus source is one of diammonium hydrogen phosphate, lithium phosphate, and phosphorus pentoxide, the carbon source is one of glucose, sucrose, oxalic acid, polyvinyl pyrrolidone, polyethylene glycol, and salicylic acid, and the solution is one of ethanol, ethylene glycol, acetone, and deionized water.
[0044] In some preferred embodiments, the transition metal atom Ti source is one of titanium dioxide, tetrabutyl titanate, titanium carbide, and titanium fluoride; the transition metal atom Mg source is one of magnesium carbonate, magnesium oxalate, magnesium acetate, and magnesium metaborate; the transition metal atom Mo source is one of molybdenum acetylacetonate, molybdenum carbide, molybdenum fluoride, and ammonium molybdate; the transition metal atom Nb source is one of niobium oxide, niobium pentachloride, and niobium oxalate; the transition metal atom Al source is one of aluminum acetylacetonate, aluminum metaphosphate, aluminum nitrate, and aluminum dihydrogen phosphate; the transition metal atom Cu source is one of copper citrate, copper pyrophosphate, copper acetylacetonate, and copper oxide; and the transition metal atom Ni source is one of nickel hydroxide, nickel acetylacetonate, nickel oxide, and nickel acetate.
[0045] The following are specific embodiments.
[0046] Example 1
[0047] 1. Add 3 g of lithium carbonate, 6.8 g of manganese acetate, 7.1 g of ferrous oxalate, 9.2 g of ammonium dihydrogen phosphate, 1.07 g of glucose, and 60 g of deionized water into a ball mill mixing tank, and grind at a speed of 400 rpm for 6 hours to obtain a uniform solid-liquid mixture;
[0048] 2. Add 0.18 g of titanium dioxide, 0.06 g of copper oxide, and 0.2 g of nickel acetate to the solid-liquid mixture, and grind at a speed of 400 rpm for 6 hours to obtain a solid-liquid mixture again;
[0049] 3. Dry the solid-liquid mixture in an oven at 120° C. for 24 hours to obtain a solid mixture;
[0050] 4. Grind the solid mixture at a rotation speed of 120 rpm for 15 minutes to obtain a solid powder, transfer the solid powder to a tube furnace for pre-calcination for 5 hours, and heat the tube furnace from room temperature to 350°C at a heating rate of 5°C / min to obtain a precursor;
[0051] 5. Place the cooled precursor in a beaker, stir at 80 rpm for 5 minutes, then transfer to a tube furnace, heat to 700°C at a heating rate of 5°C / min and keep warm for 8 hours, then naturally cool to room temperature to obtain a high-entropy lithium manganese iron phosphate positive electrode material.
[0052] The high entropy lithium manganese iron phosphate positive electrode material prepared in Example 1 was characterized by X-ray diffraction (XRD), Raman spectrometer (Raman), X-ray photoelectron spectrometer (XPS), scanning electron microscope (SEM), etc., and the following was obtained: Figure 1-4 The result graph is shown.
[0053] Figure 1 This is the XRD diagram of high entropy lithium manganese iron phosphate cathode material. Figure 1 It can be seen that the Bragg diffraction peaks of high entropy lithium manganese iron phosphate (LMFP-NCT) and lithium manganese iron phosphate (LMFP) are consistent with each other, and completely match the characteristic diffraction peaks of lithium iron phosphate, and there are no other impurity peaks, which proves that the introduction of manganese and other transition metal elements does not destroy the intrinsic olivine structure, forming a single solid solution phase. In addition, in contrast, the peak intensity of the diffraction peak of LMFP-NCT is higher than that of LMFP, which proves that the transition metal improves the crystallization degree of the material and is easy to generate large particles.
[0054] Figure 2 This is the Raman diagram of the high entropy lithium manganese iron phosphate cathode material. Figure 2 It can be seen that both LMFP-NCT and LMFP exhibit the Raman characteristic peaks of graphite, proving that both materials contain carbon in order to solve the problem of poor conductivity. D / G From the values of , it can be seen that the value of LMFP-NCT is slightly smaller than that of LMFP, which indicates that the introduction of transition metal elements will affect the carbon coating process and improve the conductivity.
[0055] Figure 3 This is the XPS diagram of high entropy lithium manganese iron phosphate cathode material. Figure 3 It can be seen that LMFP-NCT has obvious divalent iron peaks and divalent manganese peaks, proving that the introduction of transition metal elements does not affect the normal valence state of iron and manganese.
[0056] Figure 4 This is the SEM image of the high entropy lithium manganese iron phosphate cathode material. Figure 4 It can be seen that the maximum diameter of LMFP-NCT particles is 7 to 8 microns, and the maximum diameter of LMFP particles is 2 to 3 microns. Obviously, the particle size of LMFP-NCT is larger, which is conducive to increasing the compaction density on the positive electrode side and thus improving the energy density.
[0057] The high-entropy lithium iron manganese phosphate material prepared in Example 1 can be applied to the positive electrode of a lithium-ion battery. The lithium-ion battery includes a negative electrode sheet, a positive electrode sheet, a diaphragm, and an electrolyte that impregnates the diaphragm. The preparation method of the positive electrode sheet includes: using the high-entropy lithium iron manganese phosphate material as an active material, Super P as a conductive agent, and polyvinylidene fluoride as a binder, mixing and evenly coating them on a carbon-coated aluminum foil, and drying to form the positive electrode sheet, wherein the mass ratio of the high-entropy lithium iron manganese phosphate material, the Super P and the polyvinylidene fluoride is 7 to 8:1 to 2:1.
[0058] The high entropy lithium manganese iron phosphate material prepared in Example 1 was subjected to an electrochemical cycle life test and the following results were obtained: Figure 5 The result graph is shown.
[0059] Figure 5 This is a long cycle test diagram of high entropy lithium manganese iron phosphate positive electrode material. Figure 5 It can be seen that the capacity of LMFP-NCT after cyclic stabilization at a current density of 0.2C is about 150mAh / g, and the capacity retention rate is 98% after 150 cycles, which proves the excellent cycle stability of high-entropy lithium manganese iron phosphate, which may be due to the fact that the transition metal elements inhibit the Jan-Taylor effect of manganese elements.
[0060] Example 2
[0061] 1. Add 1.7 g lithium carbonate, 3.3 g manganese acetate, 3.4 g ferrous oxalate, 4.6 g diammonium phosphate, 1.3 g glucose, and 31 g deionized water into a ball mill mixing tank, and grind for 6 hours at a speed of 400 rpm to obtain a uniform solid-liquid mixture;
[0062] 2. Add 0.1 g of magnesium carbonate and 0.03 g of titanium dioxide to the solid-liquid mixture, and grind at a speed of 400 rpm for 6 hours to obtain a solid-liquid mixture again;
[0063] 3. Dry the solid-liquid mixture in an oven at 120° C. for 24 hours to obtain a solid mixture;
[0064] 4. Grind the solid mixture at a rotation speed of 120 rpm for 15 minutes to obtain a solid powder, transfer the solid powder to a tube furnace for pre-calcination for 5 hours, and heat the tube furnace from room temperature to 350°C at a heating rate of 5°C / min to obtain a precursor;
[0065] 5. Place the cooled precursor in a beaker, stir at 80 rpm for 5 minutes, then transfer to a tube furnace, heat to 650°C at a heating rate of 5°C / min and keep warm for 10 hours, then cool naturally to room temperature to obtain a high-entropy lithium manganese iron phosphate positive electrode material.
[0066] Example 3
[0067] 1. Add 3 g of lithium carbonate, 9.52 g of manganese acetate, 4.26 g of ferrous oxalate, 9.2 g of ammonium dihydrogen phosphate, 5.2 g of glucose, and 50 g of deionized water into a ball mill mixing tank at the same time, and grind for 6 hours at a speed of 400 rpm to obtain a uniform solid-liquid mixture;
[0068] 2. Add 0.6 g of nickel acetate and 0.06 g of copper oxide to the solid-liquid mixture, and grind at a speed of 400 rpm for 6 hours to obtain a solid-liquid mixture again;
[0069] 3. Dry the solid-liquid mixture in an oven at 120° C. for 24 hours to obtain a solid mixture;
[0070] 4. Grind the solid mixture at a rotation speed of 120 rpm for 15 minutes to obtain a solid powder, transfer the solid powder to a tube furnace for pre-calcination for 5 hours, and heat the tube furnace from room temperature to 350°C at a heating rate of 5°C / min to obtain a precursor;
[0071] 5. Place the cooled precursor in a beaker, stir at 80 rpm for 5 minutes, transfer to a tube furnace, heat to 700°C at a heating rate of 5°C / min, keep warm for 10 hours, and then naturally cool to room temperature to obtain a high-entropy lithium manganese iron phosphate positive electrode material.
[0072] In general, the present invention provides a method for preparing high-entropy lithium manganese iron phosphate. By precisely controlling the ratio of metal elements and three grindings and one stirring process, manganese, iron and other transition metal elements are cleverly mixed evenly. On this basis, a low-temperature carbonization and high-temperature calcination double-stage sintering strategy is used to prepare a high-entropy lithium manganese iron phosphate positive electrode material. The material has a high mixing entropy, forms a stable single-phase solid solution structure, effectively suppresses the Jan-Taylor effect of manganese elements, and has a capacity retention rate of up to 98% in 150 cycles, showing excellent cycle stability. The process conditions of the present invention are simple, the process is easy to control, and large-scale industrial production is easy to achieve; under the reduction of the carbon source, a cheap trivalent iron source can be used instead of a divalent iron source to reduce production costs; the solution can be recycled, is green and environmentally friendly, and has great economic benefits.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high entropy lithium manganese iron phosphate positive electrode material, characterized in that: The method comprises the following steps: adding a lithium source, a manganese source, an iron source and a phosphorus source into a mixing tank according to an atomic molar ratio, adding a certain amount of a carbon source and an appropriate amount of a solution at the same time, and grinding at high speed until fully mixed; then adding the required transition metal atoms according to the atomic percentage, and repeatedly grinding the mixture; after completion, drying the solid-liquid mixture at a high temperature, completely removing the liquid component, and obtaining a solid mixture; grinding the solid mixture for a third time to obtain a powdered sample, and then performing a low-temperature calcination and carbonization treatment to obtain a precursor; stirring the precursor and then calcining it at a high temperature for a long time to finally obtain a high-entropy lithium manganese iron phosphate positive electrode material.
2. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The atomic molar ratio of the lithium source, manganese source, iron source and phosphorus source is in the range of 1.05:0.2:0.8:1 to 1.05:0.8:0.2:1; the added amount of the carbon source is 5%-20% of the total mass of the above raw materials; the rotation speed of high-speed grinding is between 350 rpm and 500 rpm, and the time is in the range of 5 hours to 10 hours.
3. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The types of transition metal atoms required include Ti, Mg, Mo, Nb, Al, Cu, and Ni; the total atomic percentage of transition metals is 1% to 10%; the rotation speed of repeated grinding is between 350 rpm and 500 rpm, and the time is between 5 hours and 10 hours.
4. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The drying temperature is between 80°C and 160°C, and the drying time is between 12 hours and 48 hours.
5. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The rotation speed of the third grinding is between 100 rpm and 200 rpm, and the time is in the range of 10 minutes to 30 minutes; the temperature of low-temperature calcination is between 300° C. and 400° C., and the time is between 3 hours and 6 hours.
6. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The stirring speed is between 50 rpm and 100 rpm, and the stirring time is between 1 minute and 5 minutes; the high-temperature calcination temperature is between 600° C. and 800° C., and the stirring time is between 5 hours and 12 hours.
7. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 6, characterized in that: The lithium source is one of lithium carbonate, lithium acetate, lithium oxalate, and lithium hydroxide; the manganese source is one of manganese acetate, manganese carbonate, and manganese oxide; the iron source is one of ferroferric oxide, ferrous oxalate, and ferrous oxide; the phosphorus source is one of diammonium hydrogen phosphate, lithium phosphate, and phosphorus pentoxide; the carbon source is one of glucose, sucrose, oxalic acid, polyvinyl pyrrolidone, polyethylene glycol, and salicylic acid; and the solution is one of ethanol, ethylene glycol, acetone, and deionized water.
8. The method for preparing a high entropy lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 6, characterized in that: The transition metal atom Ti source is one of titanium dioxide, tetrabutyl titanate, titanium carbide, and titanium fluoride; the transition metal atom Mg source is one of magnesium carbonate, magnesium oxalate, magnesium acetate, and magnesium metaborate; the transition metal atom Mo source is one of molybdenum acetylacetonate, molybdenum carbide, molybdenum fluoride, and ammonium molybdate; the transition metal atom Nb source is one of niobium oxide, niobium pentachloride, and niobium oxalate; the transition metal atom Al source is one of aluminum acetylacetonate, aluminum metaphosphate, aluminum nitrate, and aluminum dihydrogen phosphate; the transition metal atom Cu source is one of copper citrate, copper pyrophosphate, copper acetylacetonate, and copper oxide; and the transition metal atom Ni source is one of nickel hydroxide, nickel acetylacetonate, nickel oxide, and nickel acetate.
9. A high entropy lithium manganese iron phosphate positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. An application of a high entropy lithium manganese iron phosphate positive electrode material, characterized in that: This application is the application of the high entropy lithium manganese iron phosphate positive electrode material described in claim 9 in the positive electrode material of a lithium-ion battery.
Citation Information
Cited By
Lithium manganese iron phosphate rapidly prepared based on assistance of molten salt and preparation method and application of lithium manganese iron phosphate
CN122355259A